2006
DOI: 10.1007/s00204-006-0135-8
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbon (PAH) metabolizing enzyme activities in human lung, and their inducibility by exposure to naphthalene, phenanthrene, pyrene, chrysene, and benzo(a)pyrene as shown in the rat lung and liver

Abstract: In order to survey changes and activities in the polycyclic aromatic hydrocarbon (PAH)-metabolizing enzymes implicated in lung cancer susceptibility studies, we investigated enzyme induction by 2-5-ring-sized 'biomarker' PAHs in rat liver and lung, and the activities in five human lung specimens. Naphthalene, phenanthrene, pyrene, chrysene, and benzo[a]pyrene (BaP) were administered to rats for 3 days (25-128 mg/kg/day) and the responses compared with those of model inducers. PAH treatment increased the CYP1A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…The high interindividual differences in expression may be due to multiple genetic, epigenetic, and epidemiologic factors. Tobacco smoke is itself known to contain a number of agents that can induce UGT activity, and thus an individual's smoking habits are likely to influence UGT gene expression levels and enzymatic activity (Villard et al, 1998;Elovaara et al, 2007). However, as only basic demographic information was available for the subjects from whom these specimens were obtained and the smoking habits of the individuals were unknown, deductions regarding the potential influence of tobacco smoke induction of UGT genes could not be performed.…”
Section: Evaluation and Correlation Of Ugt2b Expression 533mentioning
confidence: 99%
“…The high interindividual differences in expression may be due to multiple genetic, epigenetic, and epidemiologic factors. Tobacco smoke is itself known to contain a number of agents that can induce UGT activity, and thus an individual's smoking habits are likely to influence UGT gene expression levels and enzymatic activity (Villard et al, 1998;Elovaara et al, 2007). However, as only basic demographic information was available for the subjects from whom these specimens were obtained and the smoking habits of the individuals were unknown, deductions regarding the potential influence of tobacco smoke induction of UGT genes could not be performed.…”
Section: Evaluation and Correlation Of Ugt2b Expression 533mentioning
confidence: 99%
“…Gene-environmental interactions that magnify the polymorphic variability in the pulmonary bioactivation/detoxification capacity probably play a key role in individual susceptibility to or protection against, chemically-induced lung cancer. Hence, human exposure to PAH mixtures with a high content of BaP-type hydrocarbons confers a potentially higher health risk than PAH mixtures with a low content of pro-carcinogens (Elovaara et al, 2006).…”
Section: Metabolism Of Pah: Backgroundmentioning
confidence: 99%
“…Previous studies have confirmed that most PAHs are potential environmental endocrine disruptors and they are carcinogenic and/or mutagenic (Grimmer, 1983;Elovaara et al, 2007;Smith et al, 2007). Animal studies found that some PAHs affected the function of estrogen and were related to infertility (Kummer et al, 2008;Smith et al, 2007).…”
Section: Introductionmentioning
confidence: 93%